Sistematización de práctica profesional: Propuesta de mejora para la alta rotación del personal para la empresa TRINITY FARMS S.A.S. - Rodriguez Cubillos, Monica Andrea (Corporación Universitaria Minuto de Dios, 2022)
The following project as a degree option is carried out through systematization, where in the organization Trinity Farms S.A.S. a problem is identified when carrying out professional practices and for being part of the company. The problem found is the high turnover of personnel, through this systematization the objective is to make an improvement proposal for the high turnover of personnel for the company TRINITY FARMS S.A.S. For this, it was necessary to fully identify this rotation through historical data provided by the company's human resources area. Thanks to this information, it was possible to identify the employees with a survey and an interview with the area leaders. different reasons why people end the employment relationship with the company. Carrying out this project as an improvement proposal contributes positively to the organization, by collecting information and being able to identify the main reason or reasons for the high turnover in order to start implementing improvement strategies in the face of the most unfavorable situations, according to the different means in which the information is collected.

The following project as a degree option is carried out through systematization, where in the organization Trinity Farms S.A.S. a problem is identified when carrying out professional practices and for being part of the company. The problem found is the high turnover of personnel, through this systematization the objective is to make an improvement proposal for the high turnover of personnel for the company TRINITY FARMS S.A.S. For this, it was necessary to fully identify this rotation through historical data provided by the company's human resources area. Thanks to this information, it was possible to identify the employees with a survey and an interview with the area leaders. different reasons why people end the employment relationship with the company. Carrying out this project as an improvement proposal contributes positively to the organization, by collecting information and being able to identify the main reason or reasons for the high turnover in order to start implementing improvement strategies in the face of the most unfavorable situations, according to the different means in which the information is collected.
Desarrollar un plan de bienestar para aumentar los niveles de motivación y así poder disminuir el porcentaje de la alta rotación del personal en la organización Trinity Farms S.A
Keywords: Rotación del personal, talento humano, motivación laboral, bienestar laboral.; Staff turnove; human talent; work motivation; work well-being